The Lp_3561 and Lp_3562 Enzymes Support a Functional Divergence Process in the Lipase/Esterase Toolkit from Lactobacillus plantarum - Esteban-Torres, María; Reverón, Inés; Santamaría, Laura; Mancheño, José M.; de las Rivas, Blanca; Muñoz, Rosario (Frontiers in Microbiology, 2016)
Lactobacillus plantarum species is a good source of esterases since both lipolytic and esterase activities have been described for strains of this species. No fundamental biochemical difference exists among esterases and lipases since both share a common catalytic mechanism. L. plantarum WCFS1 possesses a protein, Lp_3561, which is 44% identical to a previously described lipase, Lp_3562. In contrast to Lp_3562, Lp_3561 was unable to degrade esters possessing a chain length higher than C4 and the triglyceride tributyrin. As in other L. plantarum esterases, the electrostatic potential surface around the active site in Lp_3561 is predicted to be basic, whereas it is essentially neutral in the Lp_3562 lipase. The fact that the genes encoding both proteins were located contiguously in the L. plantarum WCFS1 genome, suggests that they originated by tandem duplication, and therefore are paralogs as new functions have arisen during evolution. The presence of the contiguous lp_3561 and lp_3562 genes was studied among L. plantarum strains. They are located in a 8,903 bp DNA fragment that encodes proteins involved in the catabolism of sialic acid and are predicted to increase bacterial adaptability under certain growth conditions.